Comparing Global and Regional Maps of Intactness in the Boreal Region of North America: Implications for Conservation Planning in One of the World’s Remaining Wilderness Areas - Vernier, Pierre R.; Leroux, Shawn J.; Cumming, Steven G.; Lisgo, Kimberly; Esteban, Alberto Suarez; Krawchuk, Meg A.; Schmiegelow, Fiona (Frontiers in Forests and Global Change, 2022)
North America’s boreal forest contains some of the largest remaining intact and wild ecosystems in the world. However, human activities are systematically reducing its extent. Consequently, forest intactness and human influence maps are increasingly used for monitoring and conservation planning in the boreal region. We evaluated nine national and global maps to determine how well they agreed with each other and how effectively they captured recent anthropogenic disturbances. As a function of each map’s spatial coverage in North America, the area identified as intact ranged from 55% to 79% in Canada and from 32% to 96% in Alaska. Likewise, the similarity between pairs of datasets in the Canadian boreal ranged from 0.58 to 0.86 on a scale of 0-1. In total, 45% of the region was identified as intact by the eight most recent datasets. There was also variation in the ability of the datasets to account for anthropogenic disturbances that are increasingly common in the boreal region, such as those associated with resource extraction. In comparison to the recently produced high resolution Boreal Ecosystem Anthropogenic Disturbance dataset, the four human influence datasets (Human Footprint, Global Human Modification, Large Intact Areas, and Anthropogenic Biomes) omitted 59-85% of all linear disturbances and 54-89% of all polygonal disturbances. In contrast, the global IFL, Canadian IFL, and Human Access maps omitted 2-7% of linear disturbances and 0.1-5% of polygonal disturbances. Several differences in map characteristics, including input datasets and methods used to develop the maps may help explain these differences. Ultimately, the decision on which dataset to use will depend on the objectives of specific conservation planning projects, but we recommend using datasets that 1) incorporate regional anthropogenic activities, 2) are updated regularly, 3) provide detailed information of the methods and input data used, and 4) can be replicated and adapted for local use. This is especially important in landscapes that are undergoing rapid change due to development and have an active natural disturbance regime, such as the boreal forest of North America.